Bureaucratic Reform Barriers: A Case Study on the One Stop-Integrated Service Office in Bone Regency - Yusri Adi (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2018)
This research aimed at identifying the barriers to the implementation of bureaucratic reform, exploring the factors that cause these obstacles and offering some solutions to improve licens-ing administration services, this research applied the descriptive-qualitative approach using the case study design. Techniques of collecting data included interview, observation, and documen-tation. Instruments in this research, added the researcher himself (key device), an informant who was selected based on purposive sampling technique. Data analysis was based on "interactive models," including data collection, condensation, data presentation, and verifica-tion and concluding. The results showed that bureaucratic reform obstacles in licensing ser-vices, among others include, red tape and understaffing, while the internal environment in the bureaucracy and the various service user behavioral characteristics, were identified as critical barriers to bureaucratic reform. To that end, this research recommends conducting bureaucra-cy reform in all aspects, both internal to change bureaucracy itself) and external (induce changes in the characteristics of service user behavior).